Service Responsiveness Of PT. Pelabuhan Indonesia II (PERSERO) Bengkulu Branch In Responding Container Service User Complaints - Diana Tiarani; Vethy Octaviani; Indria Indria (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2023)
This study aims to determine the service responsiveness of PT Pelabuhan Indonesia II (Persero) Bengkulu Branch in responding the complaints from container service users. This research is qualitative research that uses deductive data analysis techniques. This indicates that the research method is descriptive. Service responsiveness is analyzed by applying 4 (four) main elements of responsiveness theory in service, namely (1) good attitude and communication; (2) prompt service; (3) proper service; and (4) careful service. The results showed that the complaint service for container services at P.T. Pelabuhan Indonesia II (Persero) Bengkulu Branch has contained the four elements in the theory of responsiveness. The company responds to various container customer complaints with good communication and attitude without discrimination. Submission of important information related to procedures in container and unloading activities is delivered transparently, both face-to-face and through social media in accordance with customer expectations. PT. Pelindo II (Persero) also continues to strive to respond to complaints more quickly. Even though there are complaints that have not been responded to perfectly, the company will be responsible and try to compensate for the loss of the container service users. Then, the service of complaints from container service customers has also been responded to appropriately. The company has made it easier for customers to make complaints, either through a letter of complaint submitted directly to the company or via email and social media. Next is PT. Pelindo II (Persero) Bengkulu Branch also fulfills the last element of responsiveness theory, namely careful service. This means that various complaints from container service users are taken seriously and carefully. This is done to minimize losses, both for customers and for the company itself.